P5.102 Antimicrobial Susceptibility of Neisseria Gonorrhoeae in Nanjing, China, 2011–2012. (13th July 2013) - Su, X; Le, W; Li, S; Wang, B; Rice, P
Abstract : Background: A study of gonococcal transmission from men to their female contacts has been under investigation at the STD clinic in Nanjing, China since April 2011. Men with symptomatic urethral discharge presenting for diagnosis and management have been screened for gonococcal infection and Neisseria gonorrhoeae strains isolated. Monitoring antimicrobial resistance (AMR) of N. gonorrhoeae is crucial for guiding effective treatment. Here, we report the results of amtimicrobial susceptibility testing of these gonococcal strains between April 2011 and 2012. Methods: We determined minimum inhibitory concentrations (MICs) for 334 concecutively obtained gonococcal isolates by agar dilution testing for: penicillin, tetracycline, ciprofloxacin, spectinomycin and ceftriaxone. β-lactamase production was determined by paper acidometric testing. Results: The prevalence of PPNG and TRNG was 36.53% (122/334) and 38.32% (128/334), respectively. Chromosomally-mediated resistance to penicillin and tetracycline was 87.26% (185/212) and 99.03%(204/206), respectively. Chromosomal resistance to ciprofloxacin (QRNG) was detected in 98.80% (330/334) of the isolates. All gonococcal isolates were susceptible to spectinomycin. Gonococcal isolates having ceftriaxone MICs ≥ 0.06 mg/L accounted for 27.54% (92/334); among them two isolates with MICs of 0.25 mg/L and 13 having MICs of 0.125mg/L. Conclusion: Among N. gonorrhoeae strains isolated in Nanjing, chromosomally-mediated resistance to penicillin, tetracycline and ciprofloxacin was high. Ceftriaxone and spectinomycin should be considered effective anti-microbial agents for the treatment of gonorrhoea in Nanjing, but and susceptibility of N. gonorrhoeae to these antimicrobial agents should be monitored continuously.